Efeito de condições artificiais de envelhecimento sobre pilares de zircônia tetragonal estabilizada por ítria (Y-TZP). Análise fractográfica dos modos de falha - Basílio, Mariana de Almeida [UNESP] (2015)
Most ceramic abutments are fabricated from yttria-stabilized tetragonal zirconia (Y-TZP). The objectives of this work were to assess the effects of artificial ageing conditions on the fracture load, phase stability and surface microstructure of a Y-TZP abutment, and to establish possible reasons for failure by fractographic analysis. Thirty two prefabricated Y-TZP abutments were screwed and torqued down to external hex implants and divided into 4 groups (n=8): 1 - control, 2 - mechanical cycling in water (1 x 106 cycles), 3 - autoclaving (134ºC; 5 hours; 2 bar), 4 - thermal cycling (104 cycles; 5º/55ºC). A single-load-to-fracture test was performed at a crosshead speed of 0.5 mm/min to assess the assembly's fracture load. X-ray powder diffraction (XRPD) analysis was applied to observe and quantify the tetragonal-monoclinic (t-m) phase transformation. Representative specimens were examined with high-resolution scanning electron microscopy (SEM) to observe the abutments' surface microstructure. Fractographic analysis was conducted under stereo and SEM. The fracture load data were compared using ANOVA and Tukey test (α=.05). All the ageing conditions reduced the fracture load significantly (ρ<0.001) and led to t-m transformation. Mechanical cycling reduced the fracture load more than autoclaving (ρ=0.034). The SEM detected surface flaws and micro-cracks. Fractographic features showed that failure started at the abutment regions in contact with the retention screw edges. Hydrothermal and mechanical conditions associated with their micro-fracture process were the most likely causes for strength degradation. This study established a fracture pattern at the connecting area and that the abutment screw could affect the occurrence of fractures